Functional identification of pathogenic autoantibody responses in patients with multiple sclerosis - Elliott, Christina; Jarius, Sven (Brain, 2012)
Abstract. Pathological and clinical studies implicate antibody-dependent mechanisms in the immunopathogenesis of multiple sclerosis. We tested this hypothesis
Advance access publication May 4, 2012
Gesehen am 27.06.2019